(untitled) (Sebha University Conference Proceedings, 2024)
The study of chemical kinetics is essential in predicting reaction rates and mechanisms of chemical processes. In order to assess the kinetics and thermodynamic characteristics of transesterification, sunflower oil was transesterified with methanol in the presence of a BaO catalyst to produce fatty acid methyl esters, FAME, (biodiesel). kinetic and thermodynamic studies have been conducted in the presence of optimal reaction conditions that were determined in our previous study. Thus, reactions were carried out in 20:1 (molar ratio of oil to methanol) with 4.7 % weight of the catalyst used at temperatures of 60, 65, and 70 °C and for reaction times of 60, 120, 180, and 240 min. It has been determined that the pseudo-first-order reaction is followed during the transesterification of sunflower oil. The study of biodiesel derived from sunflower oil underwent thermodynamic investigation at three distinct temperatures, specifically 60, 65, and 70 °C. The non-spontaneous nature of the endothermic transesterification process was demonstrated by the positive values of the enthalpy (∆H = +66.602 kJ mol−1) and Gibbs free energies. Furthermore, it is shown that the reaction is moving towards regulation by the negative entropy (∆S = -99.975 J K−1 mol−1).